Peningkatan Profesionalisme Guru di Madrasah - Munir, Misbah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
Nowadays, society needs towards the good quality service of education is getting higher. It becomes motivation for madrasah to improve its accountability and transparency within its management. The fist step to improve the quality of madrasah is the improvement of teachers’  professionalism.  Rationally, teacher is the main media in learning process and teacher has responsibility to develop students’ potency. There are five elements which are need to be paid attention by madrasah in improving teachers’ professionalism, such as: (1) readiness, (2) planning, (3) training, (4) implementation, (5) maintenance. Whereas strategies to improve teachers’ professionalism can be done through some ways such as : (1) Training of lesson study, (2) English Course, (3) Musyawarah Guru Mata Pelajaran(MGMP), (4) Training of Trainer and extracurricular, (5) Training of Syllabus and Learning media, (6) conducting Class Action Research, (7) Observation in other schools, (8) participation of teacher in order to improve counselors’ work, (9) Training of multimedia. The improvement ofteachers’ professionalism is not only giving impact towards the institution, but also giving impact towards teachers’ work so that teachers can be more confient within learning proccess in classroom.Keywords: professionalism of teacher.